SORD-deficient rats develop a motor-predominant peripheral neuropathy unveiling novel pathophysiological insights - Rebelo, Adriana P. (2024)
Biallelic SORD mutations cause one of the most frequent forms of recessive hereditary neuropathy, estimated to affect approximately 10,000 patients in North America and Europe alone. Pathogenic SORD loss-of-function changes in the encoded enzyme sorbitol dehydrogenase result in abnormally high sorbitol levels in cells and serum. How sorbitol accumulation leads to peripheral neuropathy remains to be elucidated. A reproducible animal model for SORD neuropathy is essential to illuminate the pathogenesis of SORD deficiency and for preclinical studies of potential therapies. Therefore, we have generated a Sord knockout (KO), Sord-/-, Sprague Dawley rat, to model the human disease and to investigate the pathophysiology underlying SORD deficiency. We have characterized the phenotype in these rats with a battery of behavioral tests as well as biochemical, physiological, and comprehensive histological examinations. Sord-/- rats had remarkably increased levels of sorbitol in serum, cerebral spinal fluid (CSF), and peripheral nerve. Moreover, serum from Sord-/- rats contained significantly increased levels of neurofilament light chain, NfL, an established biomarker for axonal degeneration. Motor performance significantly declined in Sord-/- animals starting at ~7 months of age. Gait analysis evaluated with video motion tracking confirmed abnormal gait patterns in the hindlimbs. Motor nerve conduction velocities of the tibial nerves were slowed. Light and electron microscopy of the peripheral nervous system revealed degenerating myelinated axons, de- and remyelinated axons, and a likely pathognomonic finding – enlarged “ballooned” myelin sheaths. These findings mainly affected myelinated motor axons; myelinated sensory axons were largely spared. In summary, Sord-/- rats develop a motor-predominant neuropathy that closely resembles the human phenotype. Our studies revealed novel significant aspects of SORD deficiency, and this model will lead to an improved understanding of the pathophysiology and the therapeutic options for SORD neuropathy.